EzPeasy Thermos Water Bottle / Nur Iffah Fitri Idelfitri - Idelfitri, Nur Iffah Fitri (2020)
Rise and Shine Sdn Bhd is introducing a new product to the customers with the name “EzPeasy” which is thermos water bottle with rotary compartment. Our company come out with this product because thermos water bottle one of the products that fulfil needs and wants in our daily life. “EzPeasy” is a unique bottle and customer friendly new invention that has been produced by our company that will be a new trend to everybody. Nowadays, there are a lot of people that miss out their breakfast especially busy person such as workers, students and also mothers. All of them did not get their proper meal because they always focus on work than health. Everyone knows breakfast is the important meal in our daily life. So with this new product, all busy people will have a pleasure breakfast or teatime anyhow anywhere. “EzPeasy” will help workers to have their breakfast on the road even though need to face traffic jam every day, all workers will get their convenient breakfast or teatime with their selected drinks on them and just drink it. Next for this product also suitable for students, because huge number of students that miss out their breakfast especially. This product helps them for having a breakfast while in class or anywhere. This product also will be needs for student when they stay up late for examination or study, because students always have an issue to get hot water during night. This thermos water bottle functions simply with help of the solar energy to make the water stay in hot condition so it will not be any issue for students or mothers that need hot water for uses. There will have a variety of design and colours according to customers demand. In extra this thermos water bottle will attached with rotary compartment that provide convenient for customer. We will introduce this technology to public, in order to reduce electrical usage in domestic daily due to the global warming nowadays. This “EzPeasy” has functions and advantages not found in today’s common thermos water bottle, thus providing a competitive advantage over more established competitors. Overall marketing strategy will be included specific marketing philosophy and strategy of the company, the value chain and the channel of distribution if the target market. Firstly, our target markets will be focusing on shop especially in Cheras area and thru our website. Our main target group of customer that would buy our products is mothers, office worker and finally will be students. The price of this product is RM 186.00 it is affordable and reasonable. The target production of our company for the following year is RM 180,000.00. The management team of our company are divide into several section and each section were led by experienced and professional employee to ensure our company’s product quality and efficiency.